Sperm recovery and ICSI outcomes in men with non-obstructive azoospermia: a systematic review and meta-analysis - Corona, Giovanni; Minhas, Suks; Giwercman, Aleksander; Bettocchi, Carlo; Dinkelman-Smit, Marij; Dohle, Gert; Fusco, Ferdinando; Kadioglou, Ates; Kliesch, Sabine; Kopa, Zsolt; Krausz, Csilla; Pelliccione, Fiore; et al. (Human reproduction update, 2019)
BACKGROUND: Factor affecting sperm retrieval rate (SRR) or pregnancy rates (PR) after testicular sperm extraction (TESE) in patients with non-obstructive azoospermia (NOA) have not been systematically evaluated. In addition, although micro-TESE (mTESE) has been advocated as the gold standard for sperm retrieval in men with NOA, its superiority over conventional TESE (cTESE) remains conflicting. OBJECTIVE AND RATIONALE: The objective was to perform a meta-analysis of the currently available studies comparing the techniques of sperm retrieval and to identify clinical and biochemical factors predicting SRR in men with NOA. In addition, PRs and live birth rates (LBRs), as derived from subjects with NOA post-ICSI, were also analysed as secondary outcomes. SEARCH METHODS: An extensive Medline, Embase and Cochrane search was performed. All trials reporting SRR derived from cTESE or mTESE in patients with NOA and their specific determinants were included. Data derived from genetic causes of NOA or testicular sperm aspiration were excluded. OUTCOMES: Out of 1236 studies, 117 studies met the inclusion criteria for this study, enrolling 21 404 patients with a mean age (± SD) of 35.0±2.7 years. cTESE and mTESE were used in 56 and 43 studies, respectively. In addition, 10 studies used a mixed approach and 8 studies compared cTESE with mTESE approach. Overall, a SRR per TESE procedure of 47[45;49]% (mean percentage [95% CI]) was found. No differences were observed when mTESE was compared to cTESE (46[43;49]% for cTESE versus 46[42;49]% for mTESE). Metaregression analysis demonstrated that SRR per cycle was independent of age and hormonal parameters at enrolment. However, the SRR increased as a function of testis volume. In particular, by applying ROC curve analysis, a mean testis volume higher than 12.5 ml predicted SRR >60% with an accuracy of 86.2%±0.01. In addition, SRR decreased as a function of the number of Klinefelter’s syndrome cases included (S=−0.02[−0.04;−0.01]; P<0.01. I =0.12[−0.05;0.29]; P =0.16). Information on fertility outcomes after ICSI was available in 42 studies. Overall, a total of 1096 biochemical pregnancies were reported (cumulative PR =29[25;32]% per ICSI cycle). A similar rate was observed when LBR was analysed (569 live births with a cumulative LBR = 24[20;28]% per ICSI cycle). No influence of male and female age, mean testis volume or hormonal parameters on both PR and LBR per ICSI cycle was observed. Finally, a higher PR per ICSI cycle was observed when the use of fresh sperm was compared to cryopreserved sperm (PR =35[30;40]%, versus 20[13;29]% respectively): however, this result was not confirmed when cumulative LBR per ICSI cycle was analysed (LBR =30[20;41]% for fresh versus 20[12;31]% for cryopreserved sperm). WIDER IMPLICATIONS: This analysis shows that cTESE/mTESE in subjects with NOA results in SRRs of up to 50%, with no differences when cTESE was compared to mTESE. Retrieved sperms resulted in a LBR of up to 28% ICSI cycle. Although no difference between techniques was found, to conclusively clarify if one technique is superior to the other, there is a need for a sufficiently powered and well-designed randomized controlled trial to compare mTESE to cTESE in men with NOA.
Gesehen am 04.03.2020